2020
DOI: 10.1111/dar.13221
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the extent to which drinking motives and problem alcohol consumption vary as a function of deprivation, gender and age

Abstract: Introduction. Existing research points to a link between socioeconomic factors, alcohol consumption and harms, while another body of work documents the importance of varying motivations to drink in shaping alcohol behaviours. Yet, little is currently known about the extent to which alcohol consumption may be differentially associated with drinking motives as a function of deprivation, gender and age. Methods. Cross-sectional analysis of data from a UK sample aged between 18 and 75 years (n = 1639; 51% male, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(74 reference statements)
1
3
0
Order By: Relevance
“…Indeed, this research links theoretically with the self-medication hypothesis [ 24 ] that posits that alcohol is used as a means of improving low mood and/or ameliorating negative affective state or mental/physical states (although see [ 25 ], which suggests that a model of affect intensity regulation may be a more advantageous way of understanding the alcohol-mood nexus, rather than theorising about mood valence). It also aligns with pre-COVID research by [ 26 ] indicating that coping, enhancement, and conformity, but not social, motives were associated with problem alcohol consumption in the UK. This study also found that coping motives in people with working class backgrounds were related to elevated alcohol consumption.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Indeed, this research links theoretically with the self-medication hypothesis [ 24 ] that posits that alcohol is used as a means of improving low mood and/or ameliorating negative affective state or mental/physical states (although see [ 25 ], which suggests that a model of affect intensity regulation may be a more advantageous way of understanding the alcohol-mood nexus, rather than theorising about mood valence). It also aligns with pre-COVID research by [ 26 ] indicating that coping, enhancement, and conformity, but not social, motives were associated with problem alcohol consumption in the UK. This study also found that coping motives in people with working class backgrounds were related to elevated alcohol consumption.…”
Section: Introductionsupporting
confidence: 88%
“…The initial model had paths from age, gender and social grade to all three components of life disruption [Employment location, Subjective mental health, Employment security], and paths from these predicting each of the drinking motives, which in turn predicted alcohol consumption (see S1 Table in S1 File ). Covariances were also present between all drinking motives (as per [ 26 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations